2022
DOI: 10.1039/d2cc00344a
|View full text |Cite
|
Sign up to set email alerts
|

Current electrochemical approaches to selective deuteration

Abstract: The selective deuteration of organic molecules through electrochemistry is proving to be an effective alternative to conventional 2H labelling strategies, which traditionally require high temperatures, high pressures of deuterium gas...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 55 publications
0
25
0
1
Order By: Relevance
“…[41][42][43][44] However, it has been demonstrated that there is substantial market potential to implement electrosynthetic routes as an alternative to traditional thermochemical approaches, for the sustainable production of organic chemicals, such as is the case with the Simons fluorination process, 45 the Monsanto adiponitrile process, 46 and electrochemical deuteration methods. 47 On a more fundamental level, electrochemistry uses an electrical current to drive, otherwise endergonic, chemical reactions. This electricity is supplied to an electrochemical cell, which consists of two complementary electrodes and a suitable electrolyte.…”
Section: Beyond Small Molecule Activation: Sac-driven Organic Electro...mentioning
confidence: 99%
See 1 more Smart Citation
“…[41][42][43][44] However, it has been demonstrated that there is substantial market potential to implement electrosynthetic routes as an alternative to traditional thermochemical approaches, for the sustainable production of organic chemicals, such as is the case with the Simons fluorination process, 45 the Monsanto adiponitrile process, 46 and electrochemical deuteration methods. 47 On a more fundamental level, electrochemistry uses an electrical current to drive, otherwise endergonic, chemical reactions. This electricity is supplied to an electrochemical cell, which consists of two complementary electrodes and a suitable electrolyte.…”
Section: Beyond Small Molecule Activation: Sac-driven Organic Electro...mentioning
confidence: 99%
“…41–44 However, it has been demonstrated that there is substantial market potential to implement electrosynthetic routes as an alternative to traditional thermochemical approaches, for the sustainable production of organic chemicals, such as is the case with the Simons fluorination process, 45 the Monsanto adiponitrile process, 46 and electrochemical deuteration methods. 47…”
Section: Beyond Small Molecule Activation: Sac-driven Organic Electro...mentioning
confidence: 99%
“…14 Electrochemical methods are gaining momentum to achieve siteselective isotopic labelling with yields varying from <5% to nearly 100% via, for example, deutero-halogenation and reductive amination reactions. 15 In addition, photocatalysis has also been used as a green chemistry alternative for the deuteration of organic compounds. 16 Starting from the final product, isotopic 2 H enrichment of labile sites such as NHn (n=1-3) and OHn (n= 1, 2) groups can be achieved by treating them with deuterated solvents or gases at moderate/elevated temperatures and pressures.…”
mentioning
confidence: 99%
“…9,13 Dual-protein catalysis has been shown to deuterate C α and C β sites in amino acids. 14 Electrochemical methods, 15 and photocatalysis have also been used as a green chemistry alternative for the deuteration of organic compounds. 16 Isotopic 2 H enrichment of labile sites such as NH n ( n = 1–3) and OH n ( n = 1, 2) groups can be achieved by treating the samples with deuterated solvents, facilitating the NMR analysis of biomacromolecules, 17 though it leads to low yields of deuteration.…”
mentioning
confidence: 99%
“…13 a Inspired by previous studies on hydrofunctionalization, 14 herein, we design the metal-free electrochemically induced hydro/deuterophosphonylation of electron-rich alkenes with P(O)H compounds to provide Markovnikov adducts with high regioselectivity (Scheme 1b). Considering the important applications of deuterated compounds in the pharmaceutical industry and scientific research, 15 we add cheap D 2 O as a deuterium source in the designed electrochemical system to synthesize a series of monodeuterated organophosphorus compounds with high D incorporation (Scheme 1b).…”
mentioning
confidence: 99%